"Um posto de combate e uma tribuna de doutrina" : o Partido Libertador e o Jornal Estado do Rio Grande (1929-1932) - Flores, Ericson (2009)
The purpose of this work is to show the relationship of the Liberator Party (PL) with respect to the movement of revolution which delivered the presidency of Brazil to Getúlio Vargas in October of 1930. The research source used for the work was basically the newspaper State of Rio Grande, the official journal of this party. This periodical, in its initial stage, was published from October, 1929 to July, 1932. The editorial columns of the paper, in particular, were analyzed, since they revealed the opinions of the paper, and thus of the PL itself. This political association had been organized in March of 1928, bringing together three distinct streams of thought: the historic federalists, the supporters of Assis Brasil, and the dissidents of the Republican Party of Rio Grande (PRR). These represented a segment of the oligarchy of the state of Rio Grande do Sul, being strongly concentrated in the southern region of the state, where the ranching industry predominated, with its large ranches dedicated primarily to cattle-ranching. When the name of Getúlio Vargas appeared as a candidate for the presidency of the Republic, as a result of a conflict between São Paulo and Minas Gerais, the liberators decided to support him. At that time there was formed around the candidacy of Vargas a union of the two political powers of the gaucho state. This Liberal Alliance was defended by State of Rio Grande, which praised its democratic principles. However, after the electoral defeat of the candidates, who opposed the federal government, there followed months of revolutionary conspiracy. It was in this time period that these leaders of political opposition allied themselves with the lieutenants. And at that time the liberator journal made harsh criticisms of the president of the Republic, Washington Luís, giving its support to the revolutionary movement. In November of 1930, after only a few weeks of struggle, and almost without resistance, Getúlio Vargas was inaugurated as head of the provisory government. And it is at this moment that a clash begins among the new power-holders: the political traditionalists with their liberal leanings and the lieutenants with their authoritarian tendencies. The liberators begin a campaign in favor of an immediate reconstitutionalization of the country and against a prolonging of the dictatorship, which is upheld by the lieutenants. The newspaper of the PL becomes a spokesman for the constitutionalist movement in the state of Rio Grande do Sul, until finally breaking completely with Vargas in the first half of 1932. 7 In July of the same year, the journal gives its support to the constitutionalist faction in the state of São Paulo in its Constitutionalist Revolution, and its main leaders are forced to flee the country